Analisis Ekonomi Pancasila Dan Implikasinya Dalam Pembelajaran Ekonomi - Mica Siar Meiriza; Syaqinah Ujung; Nurita Pasaribu; Hotman Siboro; Desry R Tarigan (Journal on Education, 2024)
Pancasila economics is an economic system that places social justice, humanity and shared prosperity as the main foundation in regulating economic activities. This article aims to analyze the concept of Pancasila Economics and how its application can be integrated into economic learning in Indonesia. This research uses a descriptive-analytical method with a qualitative approach, focusing on secondary data sources in the form of journal articles, books and official documents. The research results show that integrating Pancasila values ​​in economic education can strengthen students' character in cognitive, affective and psychomotor aspects. Learning that is oriented towards Pancasila values ​​helps form a generation that is not only technically competent, but also has moral responsibility in facing global economic challenges. It is hoped that the integration of Pancasila Economics in the economic curriculum in schools and universities will be able to create a more inclusive, just and sustainable economic system in the future